2011
DOI: 10.1371/journal.pone.0022712
|View full text |Cite
|
Sign up to set email alerts
|

ApoB100/LDLR-/- Hypercholesterolaemic Mice as a Model for Mild Cognitive Impairment and Neuronal Damage

Abstract: Recent clinical findings support the notion that the progressive deterioration of cholesterol homeostasis is a central player in Alzheimer's disease (AD). Epidemiological studies suggest that high midlife plasma total cholesterol levels are associated with an increased risk of AD. This paper reports the plasma cholesterol concentrations, cognitive performance, locomotor activity and neuropathological signs in a murine model (transgenic mice expressing apoB100 but knockout for the LDL receptor [LDLR]) of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Our results are in line with previous reports, demonstrating no significant differences in lipid profiles between young adult and middle‐aged LDLr −/− mice . However, some studies have showed that aged LDLr −/− mice, instead of the young adult, present evident atheroma plaques of considerable size, suggesting that high cholesterol levels act synergistically with aging in the evolution of atherosclerosis …”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous reports, demonstrating no significant differences in lipid profiles between young adult and middle‐aged LDLr −/− mice . However, some studies have showed that aged LDLr −/− mice, instead of the young adult, present evident atheroma plaques of considerable size, suggesting that high cholesterol levels act synergistically with aging in the evolution of atherosclerosis …”
Section: Discussionsupporting
confidence: 93%
“…In this regard, Daniel Zamb on and colleagues [1] recently reported that middle-aged patients with FH exhibit a particularly high incidence of mild cognitive impairment (MCI), a transitional state between the cognitive decline observed in the elderly and proper dementia. Of note, Ramirez and colleagues [2] and we [3] corroborated this observation in ApoB100/LDLr À/À and LDLr À/À experimental mouse models of FH, respectively. Specifically, we found that middle-aged LDLr À/À mice exhibited working, spatial reference, and procedural memory impairments without alterations in exploratory activities and anxiety-related responses.…”
supporting
confidence: 78%
“…Patients with familial hypercholesterolemia tend to have a higher incidence of MCI [77], which was corroborated by experimental studies using a rodent model of familial hypercholesterolemia, the ApoB100/LDLr -/mouse strain [78]. In the present study, we provide new evidence that aged LDLr -/mice, which are exposed to over three-fold cholesterol levels from early life, exhibit working, spatial reference, and procedural memory impairments, without alterations in exploratory activities and anxiety-related responses (data not shown), which were related to impaired function in cognition-relevant brain areas, such as the prefrontal cortex and hippocampus.…”
Section: Discussionmentioning
confidence: 68%